The Influence of Work Discipline, Job Satisfaction and Work Motivation on Employee Performance in Development Institutions East Java Province Construction Services - Awali Prasetya Hanif; Sri Utami Ady (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2022)
The formulation of the problem in this study is how the influence of work discipline, job satisfactionand work motivation on the performance of East Java Province Construction Services employees (East Java LPJK). This research is to identify and analyze the effect of work discipline, job satisfaction and employee motivation on employee performance. Meanwhile, the theory used in this study is the theory of work discipline, job satisfaction theory, motivation theory and performance theory. Meanwhile, this research was conducted at the East Java LPJK. This type of descriptive-quantitative research uses the census method, where the entire population of 50 people is used as a sample in the study. The nature of the research is explanatory research. Testing the hypothesis using multiple linear regression analysis using a confidence level of 95 percent.The results showed that the independent variables (work discipline, job satisfaction and employee motivation) simultaneously had a significant and positive effect on employee performance at LPJK East Java. Meanwhile, partially each variable has a significant effect on employee performance. As for work discipline, it is the most dominant factor influencing employee performance at the East Java LPJK, meaning that employee work discipline plays the most dominant role in determining employee performance at East Java LPJK. The results of hypothesis testing show that the coefficient of determination is 0.618, so in this case it shows that 61.8% of the independentvariables (work discipline, job satisfaction and work motivation) can be explained in the dependent variable (employee performance) at LPJK East Java,